Blood mean platelet volume and platelet lymphocyte ratio as new predictors of hip osteoarthritis severity. Issue 6 (February 2017) - Taşoğlu, Özlem; Şahin, Ali; Karataş, Gülşah; Koyuncu, Engin; Taşoğlu, İrfan; Tecimel, Osman; Özgirgin, Neşe
Abstract : Abstract: Osteoarthritis (OA) is a low grade systemic inflammatory disease in which many inflammatory mediators are known to be elevated in the peripheric blood. Blood platelet lymphocyte ratio (PLR) and mean platelet volume (MPV) are accepted as novel markers in many of the systemic inflammatory disorders, but have not been investigated in synovitis-free radiographic OA yet. The aim of this study was to evaluate the levels of blood PLR and MPV in radiographic hip OA. A total of 880 patients were evaluated retrospectively and after certain exclusion criteria, 237 of them who have primary hip OA were included. Age, sex, height, weight, body mass index, neutrophil, lymphocyte and platelet counts, erythrocyte sedimentation rate (ESR), PLR, and MPV levels were recorded, Kellgren–Lawrence (KL) grading of the hip joints were performed. Patients were then divided into 2 groups as KL grades 1 to 2 (mild–moderate) and KL grades 3 to 4 (severe) hip OA. Mean age, mean neutrophil, lymphocyte and platelet counts, mean MPV, mean PLR, and mean ESR were statistically significantly different between mild/moderate hip OA group and severe hip OA group. In univariate analysis, older age and higher MPV, PLR, and ESR were severely associated with severe hip OA. In multiple logistic regression analysis, MPV, PLR, and ESR emerged as independent predictors of severe hip OA. The results of the present study, for the first time in the literature, suggest blood PLR and MPV as novel inflammatory markers predicting the radiographic severity of hip OA in the daily practice.